Does inflation provide a more accurate expected return than sharia bonds? - Harold Kevin Alfredo (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Expected return is an important factor for investors in determining their portfolio strategy. Islamic bonds (sukuk) and inflation are often used as indicators in determining the expected rate of return. However, there is a challenge in determining which instrument is more accurate in describing the expected return. This study aims to test the Carhart Four Factor model with Islamic bonds and inflation as a substitute for Rf. This study uses a quantitative research method using MAD and determines the effect of each research variable using linear regression. The quantitative method was chosen in this study because it is appropriate for measuring and analyzing the relationship between numerical variables objectively and systematically. The results show that sukuk is superior to inflation in terms of expected return accuracy. Although inflation provides accurate results in some portfolios, especially in 2018 and 2021, sukuk consistently shows better accuracy in other years. These findings have significant implications for Islamic finance theory, indicating that sukuk can be a more reliable investment instrument in return planning.